How Can We Assess The Relation Between Equipment, Price and Electricity Demand in Tunisia? - Gam, Imen; Rejeb, Jaleleddine Ben (International Journal of Energy Economics and Policy, 2012)
Economists and analysts of electricity demand sector believed for a long time that equipment is a key factor. They try to determine the performance of Equipment policy instrument on energy demand. For lack of reliable data, they use in most cases the variable “urbanization rate” as proxy to the variable “equipment”. To assess the effectiveness of this policy as a tool to decrease electricity demand in Tunisia, we estimate a Translog production function “KLEM” using annual data spanning the period 1990-2007. The results suggest that an Equipment policy like a price policy play a crucial role in reducing electricity demand. Furthermore, those results highlight the complementary relation between electricity and equipment in the economic sense. Keywords: Electricity demand; Equipment policy instrument; Price policy; KLEM model; Complementary JEL Classifications: Q41